Severe right ventricular outflow tract obstruction caused by non-hodgkin lymphoma: complete regression after one course of bendamustine/rituximab therapy - Konstandin, Mathias; Korosoglou, Grigorios; Hosch, Waldemar P.; Hardt, Stefan; Katus, Hugo; Mereles, Derliz (Journal of the American Society of Echocardiography, 2011)
We present the case of a 67-year-old woman presenting with symptoms of predominantly right heart failure caused by cardiac tumor infiltration. Echocardiography showed almost complete obstruction, particularly of the right ventricular outflow tract. After complete diagnostic workup, treatment with only one course of bendamustine and rituximab resulted in complete resolution of the obstruction. Right ventricular outflow tract restriction due to infiltrative large B-cell lymphoma is a rare finding. Compression of the heart and great vessels, such as by mediastinal tumors, is not as rare. Prompt and accurate diagnosis by echocardiography and immediate initiation of treatment can be lifesaving.
Available online 25 October 2010
Gesehen am 07.07.2022